2023
DOI: 10.3390/ijms24033038
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Insight into Lichen Planus Immunopathogenesis

Abstract: Lichen planus is a chronic disease affecting the skin, appendages, and mucous membranes. A cutaneous lichen planus is a rare disease occurring in less than 1% of the general population, while oral illness is up to five times more prevalent; still, both forms equally impair the patient’s quality of life. The etiology of lichen planus is not entirely understood. Yet, immune-mediated mechanisms have been recognized since environmental factors such as hepatitis virus infection, mechanical trauma, psychological str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 134 publications
0
20
0
Order By: Relevance
“…These vaccines may consequently induce an increase in some skin conditions brought on by the aforementioned factors. [ 9 ] In addition to lichen planus, we may also see flare-ups of pemphigus, psoriasis, vitiligo, atopic dermatitis, neutrophilic dermatoses, acne vulgaris and certain connective tissue diseases. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…These vaccines may consequently induce an increase in some skin conditions brought on by the aforementioned factors. [ 9 ] In addition to lichen planus, we may also see flare-ups of pemphigus, psoriasis, vitiligo, atopic dermatitis, neutrophilic dermatoses, acne vulgaris and certain connective tissue diseases. [ 10 ]…”
Section: Discussionmentioning
confidence: 99%
“…The role of NK cells in OLP pathogenesis remains unclear; however, previous studies have reported that NK cells constituted 2.3–15% of cellular infiltrates in cutaneous lichen planus [ 14 , 53 ]. Therefore, NK cells may provide an early stimulatory signal for the mobilization of CD4 + and CD8 + T cells upon their arrival in lichen planus-inflamed areas [ 54 ]. Our data from the bioinformatics analysis suggest the possibility of NK cell involvement in OLP pathogenesis, which may support the hypothesis mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Mental stressors have the potential to induce atypical alterations in inflammatory factors, leading to immune dysfunction, which may contribute to the development of LP, as immune-mediated mechanisms of LP are well recognized ( 14 ). Some studies have also suggested that people with schizophrenia may have a higher risk of autoimmune diseases ( 15 ).…”
Section: Introductionmentioning
confidence: 99%